Library cooperation practices of university libraries in Ghana - Alemna, A.A.; Antwi, I.K. (International Library Review, 1990)
Library cooperation is not a new concept in the history and practice of librarianship. This paper reviews the concept of library cooperation in the United Kingdom, United States of America, Nigeria and Ghana, with specific reference to areas of cooperation among university libraries in Ghana. The major areas of cooperation such as inter-library loan service, photocopying of documents and exchanges of materials are discussed. Problems of cooperation such as the poor communication network in Ghana and inadequate materials are also highlighted. Recommendations are made for the improvement of the level of cooperation in the university libraries. These include the need to establish a National Library in Ghana; the removal of all psychological and socio-economic barriers to cooperation; and the improvement of the communication system among libraries in Ghana.
Keywords: Library cooperation; Librarianship; University libraries; inter-library loan service